A perspective on first assisting in cardiovascular operations. Issue 4 (9th June 2022) - Roberts, Charles Stewart; Westcott, Lauren Zammerilla
Abstract: The quality of surgical assistance is an important factor affecting surgical performance and outcomes. This article gives a perspective on key principles of first assisting, specifically during cardiovascular operations. The principles start with operative techniques, then expand into concepts relating to the surgical field and operating room. By adhering to the described principles, the first assistant may enhance a surgical operation, benefiting the surgeon, the operating room team, and, most important, the patient.